Frequency-dependent stimulated and post-stimulated voltage control of magnetism in transition metal nitrides: towards brain-inspired magneto-ionics. Issue 1 (28th October 2022) - Tan, Zhengwei; de Rojas, Julius; Martins, Sofia; Lopeandia, Aitor; Quintana, Alberto; Cialone, Matteo; Herrero-Martín, Javier; Meersschaut, Johan; Vantomme, André; Costa-Krämer, José L.; Sort, Jordi; Menéndez, Enric
Abstract : A voltage-controllable N ion accumulation effect at the outer surface of CoN films, enabling 'post-stimulated' learning or forgetting under deep sleep (once voltage stimuli are off), is demonstrated, triggering the development of synapse emulation. Abstract : Magneto-ionics, which deals with the change of magnetic properties through voltage-driven ion migration, is expected to be one of the emerging technologies to develop energy-efficient spintronics. While a precise modulation of magnetism is achieved when voltage is applied, much more uncontrolled is the spontaneous evolution of magneto-ionic systems upon removing the electric stimuli ( i.e., post-stimulated behavior). Here, we demonstrate a voltage-controllable N ion accumulation effect at the outer surface of CoN films adjacent to a liquid electrolyte, which allows for the control of magneto-ionic properties both during and after voltage pulse actuation ( i.e., stimulated and post-stimulated behavior, respectively). This effect, which takes place when the CoN film thickness is below 50 nm and the voltage pulse frequency is at least 100 Hz, is based on the trade-off between generation (voltage ON) and partial depletion (voltage OFF) of ferromagnetism in CoN by magneto-ionics. This novel effect may open opportunities for new neuromorphic computing functions, such as post-stimulated neural learning under deep sleep.